Training Need Analysis of Faculty Members of SAMETIs - G. Jaya; Dileep Kumar. G (Journal of Agricultural Extension Management, 2020)
Training is a proactive, planned and continuous process of change and development for an individual and also organization as a whole. Through training, an individual can acquire new knowledge, improve skills, reorient and redesign his/her attitude for growth and efficiency together with the organizational effectiveness and development. Training helps in changing the internal dynamics of an individual to cope up with the changing scenario in the organization and society. Thus, Training is an essential part of any organization. Training Need analysis (TNA) is the first and foremost step in designing the training programs for targeted group of participants. TNA gives an opportunity to assess the training needs of the participants for whom the training is to be conducted. TNA helps to identify the specific themes or topics among several themes/topics in which the participants are interested to take training. The article analyzes the training needs of faculty members of State Agricultural Management and Extension Training Institutes (SAMETIs).Five competency areas viz, training related competencies, technical competencies, administrative competencies, HRM competencies and soft skills related competencies are identified to elicit the felt needs of SAMETI faculty members. A total of 64 faculty members from 19 SAMETIs participated in the study. Relative Importance Index (RII) procedure was employed to analyze the data. The study results indicate different combination of training needs that may directly be beneficial for the SAMETI faculty to train upon and in turn beneficial for the extension functionaries and farmers for whom SAMETIs organize training programs. Further, the findings may help the capacity building institutes in preparing the training calendars and themes to be included in the refresher trainings for the SAMETI faculty members